2021
DOI: 10.1017/wet.2021.50
|View full text |Cite
|
Sign up to set email alerts
|

Integrated weed management in transplanted rice: options for addressing labor constraints and improving farmers’ income in Bangladesh

Abstract: In Bangladesh, weeds in transplanted rice are largely controlled by labor-intensive and costly manual weeding, resulting in inadequate and untimely weed control. Labor scarcity coupled with intensive rice production has triggered increased use of herbicides. These factors warrant a cost-effective and strategic integrated weed management (IWM) approaches. On-farm trials with transplanted rice were conducted during monsoon (‘Aman’) season in 2016 and 2017 and winter (‘Boro’) season in 2016 to 2017 in agroecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…). Chinnamuthu et al [73] also reported that pre emergence application of pretilachlor at 0.45 kg a.i. ha -1 on 3 DAS + roto cylindrical weeder weeding on 45 DAS resulted in the least total weed density and weed dry weight.…”
Section: Effect Of Integrated Weed Management On Yield and Yield Para...mentioning
confidence: 97%
“…). Chinnamuthu et al [73] also reported that pre emergence application of pretilachlor at 0.45 kg a.i. ha -1 on 3 DAS + roto cylindrical weeder weeding on 45 DAS resulted in the least total weed density and weed dry weight.…”
Section: Effect Of Integrated Weed Management On Yield and Yield Para...mentioning
confidence: 97%
“…This contrasts with the use of human labor for weed control in CT and FP, contributing to the 26-39% and 28-41% reduction in the person-days ha -1 required to grow these crops under CA and SAT, respectively. However, given the general low-degree of understanding among farmers of the potentially detrimental ecotoxicological effects of pesticide use (Shammi et al, 2018;Ahmed et al, 2021), as well as the potential for shifts in the community composition of weed species under reduced tillage and rice-maize rotations in Values in columns not separated by sources of variation sharing the same letter are significantly different according to Tukey's HSD at a = 0.5 and ns, not significant. according to Tukey's HSD (for TCE and V) or the Student's t test (for V) at a = 0.05; Trials were placed in five farmers each in Babuganj and Kalapara, and 10 in Kaliganj.…”
Section: Integrated Analysis Of Cropping Systems Performancementioning
confidence: 99%
“…Soybean is the fourth most important grain crop grown across the world [1]. As one of the most profitable agricultural products, soybean plays an important role in serving as a primary source of protein and nutraceuticals for both humans and livestock, and is produced widely around the world [2,3]. Weeds that grow spontaneously on agricultural soils compete fiercely with soybeans for light, water, and nutrients in the early stages of soybean growth, which greatly inhibits the growth of soybeans [4].…”
Section: Introductionmentioning
confidence: 99%